A New Record Of the Genus Pyrus -Subfamily Pomoideae ( Rosaceae) in Iraqi Kurdistan. - Abdul- Razaq, Rupak T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The current  research was ataxonomic  study for the species Pyrus pyraster L.  that belong to the subfamily Pomoideae from the family Rosaceae which growing wildely in Iraqi Kurdistan .The macro and micro morphology and pollen grain were studied .A wide field servay for the districts of Iraqi Kurdistan was done . According to the taxonomic references adetail study for the morphology of the leaves ,color of the corolla,calyx ,  the fruits diameters,  color and shapes,also the seed were studied  From the study of pollen grains it appeared that the pollen grains areTricolporate ,their shape in the Equatorial view was ovoid but in the pollar view they are triangular. The species Pyrus pyraster L.was recorded for the first time to Iraqi from Iraqi Kurdistan.